Relational Marketing Management and Influence on Customer Loyalty: Empirical Evidence from Islamic Banks in North Sumatra - Fitrianingsih; Lukieto Cahyadi; Limega Candrasa (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
In the era of globalization and increasing competition, the banking industry faces major challenges in maintaining customer loyalty. Islamic banks, as alternative financial institutions, have distinctive characteristics that differentiate them from conventional banks. In the context of increasingly intense competition in the banking industry, particularly among Islamic banks, it is essential for financial institutions to build strong and sustainable relationships with their customers. This study aims to analyze the influence of relationship marketing management on increasing customer loyalty in Islamic banks operating. The research employs a quantitative approach using a survey involving 200 Islamic bank customers. The collected data were analyzed using descriptive statistical techniques and linear regression to measure the influence of relationship marketing management variables such as communication, trust, and customer satisfaction on customer loyalty. The results indicate a significant positive relationship between relationship marketing management and customer loyalty. Effective communication and strengthened customer trust are key factors in building loyalty. These findings provide important implications for Islamic bank management, highlighting the need to develop improved marketing strategies that focus on long-term customer relationships to enhance customer retention and satisfaction.